Očekávání osobního přínosu subjektu z účasti v klinickém hodnocení - Norková, Olga (Časopis zdravotnického práva a bioetiky, 2012)
Participation of Human Subjects in a Clinical Trial is the fundamental part of Medical Research. Human Subject's participation depends on the willingness of the potential Subjects to volunteer in such a Clinical Trial. The Subject's motivations for the Clinical Trial participation diverse based on the different motivational factors. Patient's deciding whether to participate in a Clinical trial or not is influenced mainly by the current Patient’s health status and the possibility of the available standard therapy in the treatment of a serious or a life-threatening illness. The important role in the Patient decision process takes the close relationship Physician-Patient. There is no consensus among Scientists whether the Patient’s expected therapeutic benefit using the new medicinal product is the most motivational factor for the Clinical trial participation or not. Some of the latter research has concluded that some Patients frequently overestimate the chance of benefit from particular treatment. However the Patient's expectations of the potential therapeutic benefit do not depend on the Patient's correct understandings of the Clinical Trial purpose. The Patient’s willingness to contribute to the progress of medicine and desire to help other Patients is secondary consideration for the Clinical Trial participation which is reported in the medical journals. Especially Patients suffering from a life-threatening illness report altruistic reasons however this will not exclude them to expect the potential personal benefit as well. The indirect costs reimbursement to Patients during the Clinical Trial participation might motivate many potential participants for the Clinical Trial participation. This article sought to present the most frequent Subject's Expected Benefit from the Clinical Trial participation in the context of the Patient being engaged in Medical Research. Gaining a deeper understanding of this topic might be benefited for both Researchers and Physicians.
Keywords: spokojenost pacientů; Drug Approval; Researcher-Subject Relations; Patient Satisfaction; Human Experimentation; lékařská etika; vztahy mezi výzkumníkem a subjektem; Controlled Clinical Trials as Topic; lidé; Pharmaceutical Preparations; léčivé přípravky; Reward; klinické zkoušky kontrolované jako téma; Altruism; experimenty na lidech; schvalování léčiv; motivace; Ethics, Medical; odměna; altruismus; Motivation; Humans